2020
DOI: 10.35810/ects.v1i1.150
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the preoperative administration of sildenafil on operative and early postoperative outcome after mitral valve replacement in patients with pulmonary hypertension

Abstract: Background: Mitral valve diseases are commonly associated with pulmonary hypertension. The aim of this study was to evaluate the effect of preoperative administration of sildenafil on the outcome after mitral valve replacement in patients with pulmonary hypertension. Methods: This prospective randomized study was carried out on 67 patients who had a mitral valve replacement and associated high systolic pulmonary artery pressure more than 50 mmHg. Patients were randomized into three groups: group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…Ram et al (2019) reported that patients who received sildenafil were associated with shorter median mechanical lung ventilation time (16 vs. 19 hours, P = 0.431), intensive care unit stay (74 vs. 91 hours, P= 0.410), and total hospitalization stay (7 vs. 11 days, P = 0.009) compared to placebo. Comparable findings were also demonstrated in the study by Ibrahim et al (2020).…”
Section: Effects Of Acute Preoperative Sildenafil Treatmentsupporting
confidence: 86%
See 2 more Smart Citations
“…Ram et al (2019) reported that patients who received sildenafil were associated with shorter median mechanical lung ventilation time (16 vs. 19 hours, P = 0.431), intensive care unit stay (74 vs. 91 hours, P= 0.410), and total hospitalization stay (7 vs. 11 days, P = 0.009) compared to placebo. Comparable findings were also demonstrated in the study by Ibrahim et al (2020).…”
Section: Effects Of Acute Preoperative Sildenafil Treatmentsupporting
confidence: 86%
“…Acute sildenafil treatment showed no significant short-term benefits in reducing ventilation time or intensive care unit length of stay as shown in five studies [24,26,[28][29][30]. Acute sildenafil administration showed potential effects on inotrope requirement; such observation may be explained by the mechanism of sildenafil action, through its effects on pulmonary cyclic guanosine monophosphate which enhance the vasodilatory effect.…”
Section: Composite Clinical Scoresmentioning
confidence: 95%
See 1 more Smart Citation
“…Mitral valve disease commonly results in pulmonary hypertension, which is associated with poor prognosis during mitral valve replacement. 14,15 Mitral valve disease cause increase in left atrial pressures because of increase in pulmonary vascular resistance which in turn causes alveolar stress and remodeling of pulmonary vasculature. 16 As there are selective drugs for pulmonary vasculature, treatment of pulmonary hypertension has not been fully established.…”
Section: Discussionmentioning
confidence: 99%
“…2,7 In preoperative management of pulmonary hypertension, oral sildenafil is found very effective as it is a selective inhibitor of isoform 5 phosphodiestrase enzyme which increases in cyclic guanosine monophosphate (cGMP) levels. 8,9 Sildenafil can also be used to manage secondary pulmonary hypertension in perioperative period in patients undergoing open heart surgeries. 10 There are fewer studies on the use of oral sildenafil ragarding preoperative management of pulmonary hypertension with mitral valve disease.…”
Section: Introductionmentioning
confidence: 99%